Versatility and adaptative behaviour of the P^N chelating ligand MeDalphos within gold(i) π complexes. Issue 10 (11th February 2020) - Navarro, Miquel; Toledo, Alberto; Mallet-Ladeira, Sonia; Sosa Carrizo, E. Daiann; Miqueu, Karinne; Bourissou, Didier
Abstract : The hemilabile P^N ligand MeDalphos enables access to a wide range of stable gold(i ) π-complexes with unbiased alkenes and alkynes, as well as electron-rich alkenes and for the first time electron-poor ones. Abstract : The hemilabile P^N ligand MeDalphos enables access to a wide range of stable gold(i ) π-complexes with unbiased alkenes and alkynes, as well as electron-rich alkenes and for the first time electron-poor ones. All complexes have been characterized by multi-nuclear NMR spectroscopy and whenever possible, by X-ray diffraction analyses. They all adopt a rare tricoordinate environment around gold(i ), with chelation of the P^N ligand and side-on coordination of the alkene, including the electron-rich one, 3, 4-dihydro-2 H -pyrane. The strength of the N → Au coordination varies significantly in the series. It is the way the P^N ligand accommodates the electronic demand at gold, depending on the alkene. Comparatively, when the chelating P^P ligand ( ortho -carboranyl)(PPh2 )2 is used, gold(i ) π-complexes are only isolable with unbiased alkenes. The bonding situation within the gold(i ) P^N π-complexes has been thoroughly analyzed by DFT calculations supplemented by Charge Decomposition Analyses (CDA), Natural Bond Orbital (NBO) and Atoms-in-Molecules (AIM) analyses. Noticeable variations in the donation/back-donation ratio, CC weakening, alkene to gold charge transfer and magnitude of the N → Au coordination were observed. Detailed examination of the descriptors for the Au/alkene interaction and the N → Au coordination actually revealed intimate correlation between the two, with linear response of the MeDalphos ligand to the alkene electronics. The P^N ligand displays non-innocent and adaptative character. The isolated P^N gold(i ) π-complexes are reactive and catalytically relevant, as substantiated by the chemo and regio-selective alkylation of indoles.